Caesarean section and children's health: A quasi-experimental design. (2nd September 2019) - Polos, Jessica; Fletcher, Jason
Abstract : The prevalence of inflammatory child health conditions—such as asthma, eczema, and food allergy—and their associated costs have increased rapidly over the last 30 years. While environmental factors likely underpin these increases, recent studies explain only a fraction of the trend and rely on associational methods. Caesarean (or C-) section rates increased dramatically in the period of interest, and this method of delivery is an understudied environmental factor linked to child health outcomes via the gut microbiome. We fuse 22 years of birth cohort data from the United States National Surveys of Children's Health with C-section rates from the National Vital Statistics System generated for subgroups based on state, sex, race, Hispanic origin, and birth year. Then, we model the effects of C-section on rates of asthma, eczema, and food allergy using a quasi-experimental fixed effects design. We find that C-section significantly predicts food allergy, with qualitatively significant implications.